2020
DOI: 10.1038/s41419-020-02849-4
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia induces autophagy of endothelial cells and stimulates angiogenic effects in a hindlimb ischemia mouse model

Abstract: Although peripheral artery disease (PAD) is a major health problem, there have been limited advances in medical therapies. In PAD patients, angiogenesis is regarded as a promising therapeutic strategy to promote new arterial vessels and improve perfusion of ischemic tissue. Autophagy plays a critical role in catabolic processes for cell survival under normal and stressful conditions and plays fundamental biological roles in various cellular functions. In the present study, we showed that autophagy in endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Given that (1) autophagy plays an important role in clearing toxic cellular wastes or damaged organelles recognized and bound by p62 ( Jeong et al, 2020 ), and (2) p62 accumulation is considered a sign of impaired autophagy, we investigated the relationship between CARMIL3 and p62 in these brain areas. There was a parallel expression of p62 with CARMIL3, that is, a higher p62 expression was colocalized with a higher CARMIL3 expression in the neurons at the T2(+) and mismatch regions ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that (1) autophagy plays an important role in clearing toxic cellular wastes or damaged organelles recognized and bound by p62 ( Jeong et al, 2020 ), and (2) p62 accumulation is considered a sign of impaired autophagy, we investigated the relationship between CARMIL3 and p62 in these brain areas. There was a parallel expression of p62 with CARMIL3, that is, a higher p62 expression was colocalized with a higher CARMIL3 expression in the neurons at the T2(+) and mismatch regions ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Chenshu found that restoration of autophagic flux by RAPA intervention during ischemia can alleviate skeletal muscle injury, indicating that promoting autophagy has a potentially protective effect on IR in mice ( 29 ). In a study by In-Hye Jeong, ischemia induced autophagy in endothelial cells, and this increase in autophagy contributed to the regeneration and recovery of injured skeletal muscle ( 30 ). Wensi found that endothelial mTORC1 deletion can activate autophagy to protect against HLI injury in diabetic mice ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that hypoxia-induced autophagy serves not only as a protective mechanism for endothelial cells but also as an inducer of angiogenesis [ 55 , 56 ]. Treatment with autophagy inhibitors or downregulation of autophagy by silencing Atg5 expression markedly inhibits the migratory and tube-forming activities of endothelial cells [ 57 ]. Chandel et al.…”
Section: Reviewmentioning
confidence: 99%